TURKISH POLICY IN THE SOUTHERN CAUCASUS - GIANJUMIAN, Valeria (CENTRAL ASIA AND THE CAUCASUS, 2014)
Today, the Southern Caucasus is best described as a scene of geopolitical battles among Russia, Turkey, and Iran, as well as between the United States and the European Union. Each of the actors is pursuing its own political interests and nurturing its own ideas about the routes leading to the region’s stability and its incorporation into the world community. To achieve this and to arrive at pragmatic political decisions fully tuned to the geopolitical realities, political scientists and other experts in international relations must study and identify the geopolitical trends prevailing in the Southern Caucasus in the context of Turkish geostrategy in the region. The author analyzes the transformations in Turkey’s foreign policy based on the Zero Problems with Our Neighbors policy formulated by the republic’s former Foreign Minister Ahmet Davutoğlu, which make Turkey’s more active involvement in all spheres of its foreign political activities, building the Ankara-Tbilisi-Baku geopolitical axis as part of the Zero Problems with Our Neighbors policy, and establishing relations with Armenia a far from simple process. The first steps along this road have been taken: Turkey has formulated a Caucasus Stability and Cooperation Platform; Armenia and Turkey have signed a roadmap and the Zurich Protocols (the ratification of which was suspended by the National Assembly of Armenia), while Ankara has been seeking brokerage in the Karabakh conflict.